Single Layer Extra-Mucosal Versus Double Layer Intestinal Anastomosis for Colostomy Closure: A Prospective Comparative Study - Owaid, Layth Saleh; Al-Shahwani, Imad Wajeeh; Kamal, Zuhair B.; Hindosh, Laith Naif; Abdulrahman, Abbas Farman; Mihson, Haider Salim (AL-Kindy College Medical Journal, 2021)
Background: The main objective was to compare the outcome of single layer interrupted extra-mucosal sutures with that of double layer suturing in the closure of colostomies. Subjects and Methods: Sixty-seven patients with closure colostomy were assigned in a prospective randomized fashion into either single layer extra-mucosal anastomosis (Group A) or double layer anastomosis (Group B). Primary outcome measures included mean time taken for anastomosis, immediate postoperative complications, and mean duration of hospital stay. Secondary outcome measures assessed the postoperative return of bowel function, and the overall mean cost. Chi-square test and student t-test did the statistical analysis.. Results: Thirty-two patients were allocated to group A and 35 patients to group B. The mean time taken for anastomosis was significantly shorter in group A (23.25 ± 1.20 min in group A vs. 36.71 ± 1.93 min in group B; P<0.001). A significant shorter duration of hospital stay was seen in group A (7.00 ± 1.778 days in group A vs. 9.74 ± 1.990 days in group B; P<0.001). The detection of bowel sound was substantially quicker in group A as compared to group B (4.56 ± 0.50 days in group A vs. 6.46±0.50 days in group B; P<0.001). There was no significant discrepancy between the two groups regarding anastomotic leak rates (P= 0.543). The mean cost of double layer intestinal anastomosis method was significantly higher than that of single layer anastomosis (P<0.001). Conclusions: The use of single layer extra-mucosal anastomosis of the intestine has the advantage of taking less time, less morbidity and cost-effective to perform with the same rate of anastomotic leak in the closure of colostomy.